Combination of lipidomics and gene expression of THP-1 monocytes to indicate key anti-inflammatory compounds in rice bran oil - Kriskamol Na Jom; Nutthapol Wattanakul; Raweephorn Kaewsaen; Wasaporn Preteseille Chanput (Agriculture and Natural Resources, 2021)
Lipophilic compounds were extracted from four rice varieties: colorless (Khao Dawk Mali 105), red (Kum), purple (Riceberry) and black (Homnil). Lipidomic profiles were obtained via gas chromatography-flame ionization detection. In total, 75 peaks were identified, representing fatty acid methyl esters, free fatty acids and phytosterols. Unique lipidomic profiles were observed from each rice variety. Niosomes were fabricated from rice bran oil (RBO) using the thin film method and a ratio of RBO to Tween 80 of 1:3. RBO niosomes were measured to be approximately 200 nm in size. Lipopolysaccharide-stimulated THP-1 monocytes with different concentrations of RBO niosomes were incubated for 3 hr and 6 hr. The expressions of the pro-inflammatory genes TNF-α and IL-1β were analyzed. The results showed that RBO niosomes reduced pro-inflammatory genes in a dose-dependent manner. Principal component analysis revealed a clear correlation among three observed attributes: phytosterols, the degree of TNF-α and IL-1β gene expression reduction, and the rice variety (Homnil and Riceberry). The phytosterols responsible for RBO anti-inflammatory activity were determined using pairwise correlation, with 10 out of 12 of the identified phytosterols strongly correlated with pro-inflammatory cytokine gene reduction.